Anti-Swelling Polyelectrolyte Hydrogel with Submillimeter Lateral Confinement for Osmotic Energy Conversion - Yongxu Liu; Jiangnan Song; Zhen Liu; Jialin Chen; Dejuan Wang; Hui Zhi; Jiebin Tang; Yafang Zhang; Ningbo Li; Weijia Zhou; Meng An; Hong Liu; et al. (Nano-Micro Letters)
Highlights Ionic polymers can directly serve as high-performance ion-selective membranes when it was physically confined within submillimeter-sized cylindrical pore. The universality of this strategy is demonstrated in preparing cation/anion-selective membrane. With real seawater and river water, the output power density of a three-chamber cell on behalf of repeat unit of reverse electrodialysis system can reach up to 8.99 W m−2.